Beyond Fingal's cave : Ossian in the musical imagination - Porter, James, 1937- (Eastman studies in music, 2019)
Demonstrates the profound impact of The Poems of Ossian on composers of the Romantic Era and later: Beethoven, Schubert, Mendelssohn, Brahms, Massenet, and many others.